2020
DOI: 10.37268/mjphm/vol.20/no.1/art.569
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction Among Women at Four to Six Months Postpartum: A Study in a Primary Care Setting

Abstract: Sexual dysfunction in women is a significant health problem that harms marriage stability. Women in the Western countries were reportedly being affected by this condition after childbirth but the magnitude of the problem in our local setting is still unknown. The aim of this cross-sectional study was to determine the prevalence of women with sexual dysfunction at four to six months postpartum and its possible risk factors in an urban primary care setting. The participants were given a set of questionnaire, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Our study showed that the prevalence of FSD in sexually active married women at six months postpartum was 52.4%. This result is comparable with another local study conducted among women at four to six months postpartum in urban primary care settings in Malaysia, where the prevalence was 57% [ 25 ]. However, some developed countries had reported an even higher prevalence of FSD.…”
Section: Discussionsupporting
confidence: 86%
“…Our study showed that the prevalence of FSD in sexually active married women at six months postpartum was 52.4%. This result is comparable with another local study conducted among women at four to six months postpartum in urban primary care settings in Malaysia, where the prevalence was 57% [ 25 ]. However, some developed countries had reported an even higher prevalence of FSD.…”
Section: Discussionsupporting
confidence: 86%